Dual Crosslinking of Alginate Outer Layer Increases Stability of Encapsulation System - Somo, Sami I.; Brown, Jacob M.; Brey, Eric M. (Frontiers in Chemistry, 2020)
1 Abstract The current standard treatment for Type 1 diabetes is the administration of exogenous insulin to manage blood glucose levels. Cellular therapies are in development to address this dependency and allow patients to produce their own insulin. Studies have shown that viable, functional allogenic islets can be encapsulated inside alginate-based materials as a potential treatment for Type 1 diabetes. The capability of these grafts is limited by several factors, among which is the stability and longevity of the encapsulating material in vivo. Previous studies have shown that multilayer Alginate-Poly-L-Ornithine-Alginate (A-PLO-A) microbeads are effective in maintaining cellular function in vivo. This study expands upon the existing encapsulation material by investigating whether covalent crosslinking of the outer alginate layer increases stability. The alginate comprising the outer layer was methacrylated, allowing it to be covalently crosslinked. Microbeads with a crosslinked outer layer exhibited a consistent outer layer thickness and increased stability when exposed to chelating agents in vitro. The outer layer was maintained in vivo even in the presence of a robust inflammatory response. The results demonstrate a technique for generating A-PLO-A with a covalently crosslinked outer layer.